A Study of Some Important Issues for a Muslim in the Month of Ramadan - Saad, Hamza (Journal of religion and health, 2021)
The month of Ramadan is associated with many worships that might exhaust the weak body. The most important worships in Ramadan are fasting and prayer. Some prayers require the length of sitting and standing, in addition to prayer movements. Many Muslims are spending a long time in the mosque; sitting on the ground for reading or standing for prayer. The questionnaire is focused on those who spend a long time in the mosque. Seven attributes were considered for the understanding of what affects the worshiper's health, especially those who with chronic diseases. We found that there is a strong relationship between age and chronic diseases that may increase with the age. Also, the elderly cannot continue to pray for more than half an hour, and this is if balanced standing and sitting on a chair when is needed to prevent the disorder of the body and the emergence of symptoms of chronic disease.